„You are either a boy or a girl – there is no other choice.“ Analysis of the Biological Sex Concept in Biology Textbooks - Vasiliūnaitė, Emilija; Giniotaitė, Akvilė (Acta Paedagogica Vilnensia, 2023)
Today’s scientific discourse is increasingly criticizing the strict binary concept of biological sex. While science is progressively revealing the complexity of biological sex, the knowledge of biology for many is limited to what is acquired at school. Nonheteronormative, sex-wise atypical people still face isolation, misunderstanding and resulting social and psychological difficulties at school and in society in general. To explore the concept of biological sex presented in biology textbooks, qualitative content analysis was used. The analysis focused on the stages of sex development, the characteristics defining biological sex, the concept of sex being discrete or continuous trait, and the representation of differences in sex development. It was found that the information provided was inconsistent and superficial, failing to reflect the complexity of the sex development process. Biological sex was presented as an unambiguously discrete and binary trait, with no mention of differences in sex development. A poor understanding of biological sex does not encourage critical discussion about human biodiversity. It reproduces heteronormative norms, that condition discrimination and bullying.